Pavimento intertravado como ferramenta de moderação do tráfego nos centros comerciais de travessias urbanas - estudo de caso Guaiúba, CE - Ary Júnior, Ivan José (2007)
This research is focused on the applicability of interlocked pavement as a tool for traffic calming at commercial centers on urban sections of rural roads. It was researched a way to control vehicle speed on urban sections of rural roads that is also capable of maintaining a controlled speed throughout the critical path where accidents typically occur. The literature review indicated the characteristics and potential application of interlocked pavements, and the needs of urban sections of rural roads concerning speed control. It is evaluated the effect of interlocked pavements on traffic calming and specifically as it applies to urban sections of rural roads. The research was conducted with a group of specialists using the Delphi Technique. Moreover, it was developed a traffic simulator computer program that evaluates the behavior of drivers when passing through sections with either asphalt or interlocked blocks as the surface course. The research indicates a potential application of interlocked pavement as a traffic calming tool at the commercial center located on the urban section of the rural road at Guaiúba town, state of Ceará, on CE 060 highway.